Face transplantation in rats. Reproducibility of the experimental model in Brazil - Fábio de Freitas Busnardo; Pedro Soler Coltro; Marcelo Vitoriano Olivan; Guilherme Cardinali Barreiro; Rachel Rossine Baptista; Marcus Castro Ferreira; Rolf Gemperli (Acta Cirúrgica Brasileira, 2014)
PURPOSE:To investigate the reproducibility of the experimental model of face allotransplantation in rats in Brazil.METHODS: Eighteen rats were operated, nine-nine donors recipients. Animals underwent transplantation of the left hemiface, with periorbital and scalp. Transplants were made from donor Wistar rats to recipients Lewis rats. Flaps were based on the common carotid artery and the external jugular vein of the donor animal and the anastomosis in the recipient area was performed in common carotid artery (end-to-side) and in external jugular vein (end-to-end).RESULTS:Of the nine recipient animals operated, six survived and three progressed to death in the first days after surgery (survival rate = 67%). The mean time of the procedure was 252 minutes and the mean time of flap ischemia was 95 minutes. The five surviving animals were sacrificed at 14 days, in good general condition and without signs of tissue rejection.CONCLUSIONS:The experimental model of face allotransplantation in rats is reproducible in our midst. Duration of surgery, time of flap ischemia, animal survival rate and complications observed were similar to those described in the literature.